1985
DOI: 10.1111/j.1365-2427.1985.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history and ecological role of the xylophagous aquatic beetle, Lara avara LeConte (Dryopoidea: Elmidae)

Abstract: SUMMARY. This study documents the life history of the xylophagous elmid beetle, Lara avara, and estimates its contribution to wood degradation in Oregon streams. The life cycle was found to be 4 to 6 or more years long, with all but 2–3 months of that spent in the larval stage. Larvae grow through seven instars, taking about 1 year for instars 1–3, and from 3 to 5 or more years for instars 4–7. Last‐instar larvae leave the water to pupate. Adults live approximately 3 weeks and occur from May to August. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 16 publications
(15 reference statements)
1
32
1
Order By: Relevance
“…The high assimilation efficiencies of epixylon (26-36%) by the three detritivores were unexpected. Steedman and Anderson (1985) reported assimilation efficiencies of 4-7% for L. avara fed wood, efficiencies that were much lower than what we found. Wood consumed by L. avara was highly grooved, indicating that individuals had ingested primarily wood (Steedman and Anderson 1985).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The high assimilation efficiencies of epixylon (26-36%) by the three detritivores were unexpected. Steedman and Anderson (1985) reported assimilation efficiencies of 4-7% for L. avara fed wood, efficiencies that were much lower than what we found. Wood consumed by L. avara was highly grooved, indicating that individuals had ingested primarily wood (Steedman and Anderson 1985).…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, wood is considered to be a poor-quality food resource (Anderson and Cummins 1979). In the only published study of wood assimilation by aquatic insects, Steedman and Anderson (1985) measured assimilation efficiencies of 4-7% for Lara avara, a slowgrowing beetle species, fed alder and conifer wood. Golladay and Sinsabaugh (1991) suggested that wood biofilms (epixylon) might be overlooked sites of metabolic activity in streams.…”
mentioning
confidence: 99%
“…Epixylic fungi and bacteria derive certain amounts of N and P directly from wood (Tank & Dodds, 2003), whereas algae benefit from carbon released during degradation of wooden tissue . Nutrients liberated from CWD can also be directly used by epixylic invertebrates, including facultative xylophages Steedman & Anderson, 1985;Harmon et al, 1986); however, invertebrate consumers are mostly subsidized by biomass produced by epixylic biofilm. Some experiments have shown that wood biofilm was readily assimilated by consumers, and its abundance (particularly in terms of algae) was negatively correlated with invertebrate numbers Eggert & Wallace, 2007).…”
Section: Nutrient Cycling and Productivity In Cwd Habitatmentioning
confidence: 99%
“…The ecology of xylophages is poorly recognized and their contribution to CWD degradation was examined only in streams. According to previous studies, xylophages use their own enzymes to digest wooden tissue or they use for this purpose sequestered fungal enzymes or symbiotic bacteria and protozoans inhabiting their guts (Anderson et al, 1984;Steedman & Anderson, 1985;.…”
Section: Dynamics Of Cwd In Littoral Zonesmentioning
confidence: 99%
“…The complete larval development of aquatic insects associated with submerged wood is reported for the dipterans Lipsothrix spp. Loew, 1879 (Dudley & Anderson, 1987) and Xylotopus par (Coquillett, 1905) (Kaufman & King, 1987), the coleopterans Macronychus glabratus Say, 1825 (Phillips, 1997) and Lara avara LeConte, 1852 (Steedman & Anderson, 1985), the tropical ephemeropterans Povilla adusta Navas, 1912 and Asthenopus spp. Eaton, 1871 (Sattler, 1967;Tobias, 1996), and the trichopteran Lasiocephala basalis (Kolenati, 1848) (Hoffmann, 2000).…”
Section: Introductionmentioning
confidence: 99%